2014
DOI: 10.1037/a0033478
|View full text |Cite
|
Sign up to set email alerts
|

Social networking and professional ethics: Client searches, informed consent, and disclosure.

Abstract: As mental health professionals are increasingly using technology in their clinical work, it is important that research examines the ethical implications of online behaviors. This study examined the online hehaviors of 315 counseling and psychology graduate students. Hierarchical multiple regression was used to examine online client searches, informed consent, and disclosures. Increased disclosure of client information was related to lower scores on ethical decision-making and to program type (counseling, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…These are no longer particularly novel concepts, as this literature has developed over the past decade and states are increasingly introducing legislation to facilitate the provision of telehealth services (see, e.g., New Jersey's Bill S291/652/1954, which was recently signed into law by Governor Christie). A more contemporary issue, however, is mental health professionals' use of the Internet to gather information about their clients (see, e.g., Asay & Lal, 2014;Clinton, Silverman, & Brendel, 2010;DiLillo & Gale, 2011;Harris & Robinson Kurpius, 2014;Kaslow, Patterson, & Gottlieb, 2011;Kolmes & Taube, 2014;Lannin & Scott, 2013;Pham, 2014;Powell & Clarke, 2006).…”
Section: Mental Health Servicesmentioning
confidence: 99%
“…These are no longer particularly novel concepts, as this literature has developed over the past decade and states are increasingly introducing legislation to facilitate the provision of telehealth services (see, e.g., New Jersey's Bill S291/652/1954, which was recently signed into law by Governor Christie). A more contemporary issue, however, is mental health professionals' use of the Internet to gather information about their clients (see, e.g., Asay & Lal, 2014;Clinton, Silverman, & Brendel, 2010;DiLillo & Gale, 2011;Harris & Robinson Kurpius, 2014;Kaslow, Patterson, & Gottlieb, 2011;Kolmes & Taube, 2014;Lannin & Scott, 2013;Pham, 2014;Powell & Clarke, 2006).…”
Section: Mental Health Servicesmentioning
confidence: 99%
“…Professionalism is context dependent (Brendel et al, 2007;Harris & Kurpius, 2014;Ikkos & Mace, 2009;Malhi, 2008;Wise, 2008). Moreover, it is a dynamic construct, which shifts across time and professions (Bhugra, 2008a;Bhugra, 2010;Bhugra & Gupta, 2010;Malhi, 2008.…”
Section: # $mentioning
confidence: 99%
“…Moreover, it is a dynamic construct, which shifts across time and professions (Bhugra, 2008a;Bhugra, 2010;Bhugra & Gupta, 2010;Malhi, 2008. Variations in regulatory policy are influenced by subtle variations in individuals' beliefs and understanding (Malhi, 2008), which with case studies of professional failure, lead to ethical codes being amended and updated (Gottlieb et al, 2009;Harris & Kurpius, 2014). Mental health services are continually in reform (Bhugra & Gupta, 2011;Malhi, 2008) and clinicians have suggested that the mental health professions…”
Section: # $mentioning
confidence: 99%
See 1 more Smart Citation
“…Among graduate students in counseling and psychology, trainees who performed targeted online searches for client information indicated that curiosity was the most common reason for the search (Harris and Kurpius 2014), and other studies have found curiosity-motivated searches among psychiatrists and other mental health professionals (Deen, Withers, and Hellerstein 2013;Ginory, Sabatier, and Eth 2012). When an Internet search on a patient is unnecessary, such a search may lead to unforeseen boundary problems that may adversely affect the psychiatrist-patient relationship (Gabbard, Kassaw, and Perez-Garcia 2011; Ginori, Sabatier, and Eth 2012).…”
Section: Boundaries (Includes Coi)mentioning
confidence: 98%